2021
DOI: 10.1002/adma.202006924
|View full text |Cite
|
Sign up to set email alerts
|

Néel‐Type Elliptical Skyrmions in a Laterally Asymmetric Magnetic Multilayer

Abstract: Magnetic skyrmions, topological chiral spin textures, have aroused extensive research interests due to their intriguing topology-related physics and promising applications in spintronic devices. [1-4] In most cases, skyrmions' chiral spin textures are mainly determined by the Dzyaloshinskii-Moriya interaction (DMI), [5-7] which favors a non-collinear spin configuration between neighboring spins. The appearance of DMI is a direct consequence of spin-orbit coupling and inversion symmetry breaking. [8-10] Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…This range covers the skyrmion stability region shown in Figure . The DMI gradient can be also introduced by creating composition gradients or strains induced at interfaces due to specific deposition approaches. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This range covers the skyrmion stability region shown in Figure . The DMI gradient can be also introduced by creating composition gradients or strains induced at interfaces due to specific deposition approaches. , …”
Section: Resultsmentioning
confidence: 99%
“…The DMI gradient can be also introduced by creating composition gradients or strains induced at interfaces due to specific deposition approaches. 40,41 To characterize the DMI-gradient-driven motion, we compare it to the motion induced by a spin-polarized current. We place the skyrmion at the center of the stripe, with dimensions of 700 × 200 × 1 nm.…”
Section: Analytical Consideration Of Skyrmion Motion Based On the Thi...mentioning
confidence: 99%
“…Wilson et al 38 observed the distorted elliptical lattice state in the material Cu 2 OSeO 3 when the applied magnetic field was tilted with respect to the direction normal to the film. Cui et al 39 experimentally observed Néel-type elliptical skyrmions when they obliquely deposited one layer into a multilayer system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the magnetic configuration in the domain wall is ↑←↓, i.e., a left-handed chirality. The magnitude of DMI can be obtained by measuring the AHE loops of switching a Hall cross with combined H x and H z under a series of DC current densities [ 39 , 40 ]. Figure 2 d summarizes the SOT efficiency ( χ ) as a function of H x .…”
mentioning
confidence: 99%